Characteristics of Instant Chocolate Drink with the Addition of Natural Sweeteners Sugar Stevia Leaf Extract (Stevia Rebaudiana Botani) - Andi Eko Wiyono; Andrew Setiawan Rusdianto; Hendy Firmanto; Ekky Audina Rusita; Nita Kuswardhani; Miftahul Choiron; Hifdzil Adila (Newinera Publisher, 2022)
Instant chocolate drink is a type of processed chocolate product that has many devotees, the use of sucrose as a sweetener for flavour in the process of making instant chocolate drinks can have side effects on health, namely it can cause heart attacks, allergies, diarrhoea, increase the risk of bladder cancer, hypertension and migraines. Stevia leaves contain glycosides which have a sweetness level of 250 higher than sucrose. The purpose of this study was to determine the effect of stevia sugar as a natural sweetener in the manufacture of instant chocolate drinks. The method used is a laboratory study using a single factor at 3 levels of treatment, namely the concentration of instant chocolate and stevia sugar used as much as 11g and 7g; 9g and 9g; as well as 7g and 11g. Data analysis used two methods, namely the Chi-square method for organoleptic data and the One Way ANOVA method with a 95% confidence level followed by Duncan's New Multiple Test (DMRT). The results of this study are samples with concentrations of cocoa powder and stevia sugar as much as 11g and 7g are the best treatment by having a colour parameter value of 4.13 (like), taste parameter of 3.80 (somewhat like), aroma parameter of 4.13 (like), the viscosity parameter is 4.33 (like), the water content parameter is 4.14%, the solubility parameter is 90.15%, the pH parameter is 6.4 and the total dissolved solids parameter is 9.03.